ASLIYATDAGI PRAGMATIK XUSUSIYATLARNI TARJIMADA QAYTA YARATISH MASALALARI - Tursunbaev, B.T. (SCIENCE and SOCIETY, 2024)
This article examines the theoretical and practical significance of the issues of recreating the pragmatic features of the original in translation. When the source text is presented illegibly, the words themselves are understandable, but the overall meaning of what is said is unclear. As a rule, obscurity is investigated due to the insufficient ability of the author of the source text to express his thoughts, poor translation from one language to another.
Keywords: translation; pragmatics; linguistics; lexical-grammatical; lexical-stylistic; anthropocentric